When Doctors and Parents Disagree Ethics, Paediatrics and the Zone of Parental Discretion - Gillam, Lynn (The Federation Press, 2016)
In paediatrics, clinicians and parents sometimes disagree about the appropriate medical treatment for a child. Parents can prefer an option that differs from the clinician's recommendation. When should the parents' decision about their child's medical treatment be overridden? This book explores ethical decision-making when clinicians and parents disagree about medical treatment for a child. It develops and explores a concept called the zone of parental discretion: an ethical tool that aims to balance children's wellbeing and parents' rights to make medical decisions for their children. Written by experienced clinical ethicists and paediatric clinicians, this book offers ethical analysis and practical guidance based on real-life clinical cases. It aims to assist doctors, nurses, allied health professionals and clinical ethics staff to deal with these ethically challenging situations. The book is divided into five parts: 1. An ethical tool: the zone of parental discretion 2. Roles of doctors and parents in decision-making 3. Clinicians encountering parental refusals 4. Clinicians encountering parental requests for treatment 5. Clinicians encountering parental requests for interventions on healthy children